Analisis Tantangan Guru Dalam Pembelajaran Matematika Secara Daring di Masa Pandemi di SDN 004 Simpang Pulai Kecamatan Ukui - Rambe, Ernila Sari; Witri, Gustimal; Antosa, Zariul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to identify and describe the teacher’s challenges in teaching mathematics during the COVID-19 pandemic at SDN 004 Simpang Pulai. The subjects in this study were starting from grade 1 teachers to grade 6 teachers, totaling 6 class teachers. This type of research is descriptive qualitative research using the Miles and Huberman Model. The data collection technique used is by using an interview guide that contains questions. The results of the study indicate that the challenges of teachers iin learning mathematies online can be classified into the first two; Challenges from within, online mathematics learning which is carried out at SDN 004 Simpang Pulai. Not effective in terms of achieving learning objectives, second; Challenges from outside, low student motivation andinvolvement of parents to assist children in learning mathematics both morally and materially.